The Existence of Financial Statements on Business Performance: Literature Review - Fitriyani Syukri; Bahruddin; Fitriani; Sofyan (IECON, 2024)
This study explores the impact of financial reports on the performance of Small and Medium Enterprises (SMEs), focusing on their role in enhancing financial management, governance, access to capital, self-reliance, and competitiveness. A qualitative approach, emphasizing a literature review, was employed, with data sourced from databases such as ScienceDirect, Emerald, JSTOR, Google Scholar, and Semantic Scholar. The analysis used descriptive methods and deductive logic to extract relevant insights. Findings highlight the pivotal role of high-quality financial statements in SME performance. Reliable financial reports provide essential data for operations, enabling informed decision-making and strategic planning. This enhances business performance, credibility, transparency, accountability, and investor appeal while promoting resource management efficiency. The study emphasizes that adopting digital financial statements improves financial management efficiency, further supporting SME growth. High-quality financial reports are identified as key tools for evaluating performance and operations, contributing to improved competitiveness and sustainability. The research underscores the importance of effective financial report management, suggesting that it significantly benefits SMEs by facilitating access to funding and strengthening market competitiveness. These findings offer valuable insights for SMEs, policymakers, and stakeholders aiming to enhance the sector’s performance and resilience.